Centennials Perspective: Exploring Gender Differences on Consumer Online Behavior - Wardhanie, Ayouvi Poerna (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
To conduct the survey, 124 respondents who are between the ages of 18 and 25 and who are Dinamika University students in Surabaya and have made online purchases in the past three months were given questionnaires. A questionnaire and field observations served as the data-gathering tool for this non-test. Descriptive statistics were used to assess the acquired data using graphs and percentage computations. The findings of this study indicate that utilizing smartphones and E-money as an option of payment while purchasing on the Marketplace is more convenient for both sexes. Women are more likely to be exposed to commercials, enjoy seeing bargains, and frequently go shopping for necessities. So as to conduct the survey, questionnaires were distributed to 124 respondents from students at Universitas Dinamika in the Indonesian city of Surabaya in East Java Province. The respondents are between the ages of 18 and 25, and who have made purchases online during the last three months. Field observations and a questionnaire were used to collect data for this non-test. Graphs and percentage calculations were employed to evaluate the collected data using descriptive statistics. According to the study's findings, both sexes find it easier to pay using smartphones and e-money while making purchases on the marketplace. Men always do their research before making an online purchase, but women are more likely to see ads, enjoy buying necessities, and enjoy finding offers. They look for product returns due to incorrect shapes and colors, read reviews, and apply brand category filters.